(3WjHI GdfTQ aj GdbQGAGJ GdYTQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , (B833 (3g`s ((3YHOg ehSi Hf Ydj Gdhcjd GdOeQOGTjs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eMeO gh GHf GdLRQj jGPG GdLdGd GQMeg hGSJQ hGZaQ (B- (3GdMeO ddg Ydi eG jSQg ef fTQ efbhd MQha GdYTQg (B- (3Ke GdUdGI hGdSdGe GdSQeOj Ydi GdfHi GdeUWai eMeOs
(3BNQgG (B:s
(3hbO CLRJgG dcd ebQj cPG CLRJ cd ef ai YUQj (B- (3QhGjI HTQWgG GdeYJHQ hbGdg eMeO Hf GdLRQj (B- (3jQMeg HaVdg GdQMef aXfg ef LhOg GdZaQGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 45s
(3eYLe GdeDdajf (B3 / 687s
(3cTa GdXfhf (B2 / 1118s
(3TPQGJ GdPgH (B7 / 204s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs